The Analytical Hierarchy Process (AHP) for Best Employee Selection: Reward Implementation Strategy in Government Agencies - Umi Muzayanah; Joko Tri Haryanto; Koeswinarno Koeswinarno (Jurnal Borneo Administrator, 2023)
Reward is a strategy for empowering employees as human resources to achieve the bureaucratic reform target, namely creating civil servants' human resources with integrity, neutrality, competence, capability, professionalism, high performance, and prosperity. An appreciation of the award is giving the title of the best employee to ASN (Civil Servants), who have the best performance and achievement. Generally, the superior carries out the employee appraisal system, which is often subjective. The Office of Religious Research and Development Ministry of Religious Affairs Semarang has implemented an assessment of the best employee based on peer assessment. The article aimed to describe and discuss the process of evaluating and selecting the best employees at the Office of Religious Research and Development in Semarang. This study used a quantitative approach through the Analytic Hierarchy Process (AHP). The respondents were 38 civil servants at the Office of Religious Research and Development Semarang, consisting of 9 administrative and 29 research personnel. The findings showed that the application of AHP succeeded in selecting the two best employees, consisting of one person from the administrative staff and one from the research staff. The assessment of employees is relatively objective because a rather large number of colleagues carry it out. AHP is likely to be applied in government agencies because it is flexible, easy to understand, and can solve complex problems. Also, AHP can be used by nongovernmental institutions.